Strategic Planning as a Determinant of Business Unit Success at AMGPM Ranting Sion Jemaat Poka - Waileruny, Hulawa Theresia; Hadinda, Hadinda (Pascasarjana Universitas Mataram, 2024)
The aim of implementing this community service activity is to provide an understanding of the importance ofstrategic planningfor the success of adaptive and sustainable business unitsThe Youth of the Maluku Protestant Church (AMGPM) Zion Branch, Tiberias I, Poka Congregation. Presenting Gen Z who are in the AMGPM Zion Branch, Tiberias I, Poka Congregation, this activity is expected to be the answer to the lack ofeducation related to strategic planning, seeing more than 34% who failed to run a business. This activity is in the form of socialization on topics raised according to the theme